REDESAIN KAWASAN EKOWISATA MANGROVE DI DESA SUNGAI KUPAH - Prasetyo, Yohan; Gultom, Bontor Jumaylinda BR; Khaliesh, Hamdil (JMARS: Jurnal Mosaik Arsitektur, 2024)
Coastal areas are one of the forest ecosystems that have abundant resources because it is a combination of rich marine ecosystems and terrestrial ecosystems. One of the most important ecosystems in coastal areas with resources, ecosystems and the environment is the mangrove forest area. Mangrove forest is a coastal resource that has a high carrying capacity for life, especially from the functions it contains such as the ecosystem contained therein, natural resources and economic use. In addition to being a meeting place for marine and terrestrial ecosystems, mangrove forests can also be used as a place of conservation, tourism and education. Sungai Kakap is a sub-district in Kubu raya that has a coastal area one of which is in Sungai Kupah Village. The mangrove forest area in Sungai Kupah Village has become one of the tourist icons in Sungai Kupah Village. existing mangrove ecotourism contains beautiful mangrove forests and their ecosystems in the mangrove forest, but as a mangrove ecotourism area it lacks ideal and optimal infrastructure and supporting spaces for recreational, educational, conservative tourism and the area becomes monotonous. The development of mangrove ecotourism areas in Sungai Kupah village must be carried out with the design of the area to restore ecotourism functions and develop the potential that exists in the mangrove ecotourism area in Sungai Kupah Village.